Answer:
hole at x=-3
Step-by-step explanation:
The hole is the discontinuity that exists after the fraction reduces. (Still doesn't exist for original of course)
The discontinuities for this expression is when the bottom is 0. x^2-9=0 when x=3 or x=-3 since squaring either and then subtracting 9 would lead to 0.
So anyways we have (x+3)/(x^2-9)
= (x+3)/((x-3)(x+3))
Now this equals 1/(x-3) with a hole at x=-3 since the x+3 factor was "cancelled" from the denominator.
Answer:D)
Step-by-step explanation:
Answer:
201.06
Step-by-step explanation:
hope this helps!!!!
Answer:
$14400
Step-by-step explanation:
3600*2=7200 after the first 7 years
7200*2= 14400 after the next 7 years
17-14=3 years left after the first 14 years